An action research approach: developing intercultural competence in German Studies at Rhodes University - Collins, Morgan Gwyneth (Rhodes University, Faculty of Humanities, School of Languages, 2018)
The need to develop interculturally competent graduates is a concern for universities across the world. In South African universities this need is linked to globalization and increased diversity in terms of student demographics since 1994. Considering the legacy of apartheid, South African universities especially, and pressingly, need to respond to both global and national diversity concerns. ICC can play a significant role in creating more culturally inclusive spaces as students are provided with opportunities to "relate to and with people from vastly different cultural and ethnic backgrounds" (Spitzberg & Changnon, 2009, p. 4). In a similar way, Germany has faced, and continues to face, challenges relating to diversity especially in relation to migrants and as such, interculturality is a topic of debate in society and scholarly discourse. Therefore, ICC is as relevant to German society as it is South African society. Courses that explicitly deal with ICC are however, not common in South African universities and discourse, and as a result universities are "missing out on developing students' intercultural competence" (Deardorff & Quinlan, 2016). This thesis aimed to address this gap by investigating the viability and necessity of introducing a module that deals explicitly with ICC into the German Studies course at Rhodes University. In doing so it contributed to the creation of disciplinary knowledge as well as furthering the aim of aiding the creation of responsible global citizenship, alongside 'academic citizenship', and aiding the internationalisation at home concept by encouraging the students to understand their own lived reality in a diverse society. This research made use of an action research approach to implementing a module and tracing its development. Student responses, as well as reflection and observation, found that a module dealing explicitly with ICC was viable and able to contribute to developing students' sense of cultural self-awareness and their awareness of ICC as a set of transferrable skills and knowledges. This module aimed to serve as an introduction to ICC for students in order to begin to develop their intercultural competence and increase their awareness and critical approach to culture and intercultural encounters.
Keywords: Action research in education -- South Africa -- Makhanda; German language -- Study and teaching -- Foreign speakers; Cultural relations; Multicultural education; World citizenship